Jan-Ola Östman, Caroline Sandström, Pamela Gustavsson & Lisa Södergård (eds.), Ideologi, identitet, intervention. Nordisk dialektologi 10 - Edlund, Lars-Erik (Journal of Northern Studies, 2020)
Review of: Jan-Ola Östman, Caroline Sandström, Pamela Gustavsson & Lisa Södergård (eds.), Ideologi, identitet, intervention. Nordisk dialektologi 10, Helsinki: University of Helsinki 2017 (Nordica Helsingiensia 48; Dialektforskning 5), ISBN 9789515129963, 9789515129970, ISSN 1795-4428, 454 pp.